INFORMING STUDENTS ABOUT PROFESSIONS - Ibragimova Maryamkhan; Islamova Mohidil (International Journal of Artificial Intelligence for Digital Marketing, 2024)
The purpose of this service is to provide students with comprehensive information about the various jobs that exist, including requirements, responsibilities, career opportunities, and related industry developments. To increase students' understanding of the world of work, service methods involve career seminars, skills development workshops, industry visits, and the use of online resources. Expected outcomes include increased student knowledge of various professions, a better understanding of available career paths, and the development of skills that match job market needs. In addition, this service increases students' awareness of work